KETAHANAN BEBERAPA VARIETAS KACANG TANAH (Arachis hypogeae L.) PADA KELENGASAN TANAH - Sutoyo, Sutoyo; Agastya, I Made Indra; Astutik, Astutik (Universitas Tribhuwana Tunggadewi, 2023)
In the cultivation of peanuts in Indonesia, especially in dry land with various limited plant growth factors, the main obstacle to planting in dry land is the uncertain level of water availability. One of the efforts to overcome the problem of water availability on dry land is to plant drought-resistant peanut varieties including local superior varieties and national superior varieties that are tolerant of water shortage conditions and have high production potential. The purpose of this study was to study the resistance of several peanut varieties to soil moisture or water availability for plants.This study used a factorial randomized block design. The first factor is plant variety, consisting of V1 = hypoma-1, V2 = hypoma-3, and V3 = local, the second factor is soil moisture, consisting of K1 = 25% field capacity, K2 = 50% lang capacity, K3 = 75% field capacity and K4= Normal (100% field capacity). The results showed that the interaction between plant variety and field capacity had no significant effect on all of the observed parameters. Plant variety had a significant effect on plant height at the beginning of growth, while soil moisture had a significant effect on leaf number at the end of growth, number of pods, pod weight, seed weight per plant, 100 seed weight, and plant productivity. Soil moisture at 50% and 75% resulted in plant productivity not significantly different.